Property Rights and Environmental Policy: A New Zealand Perspective - Kevin Guerin (New Zealand Government, The Treasury, 2003)
This paper is intended to lay out a preliminary foundation for applying a property rights perspective to environmental policy issues facing New Zealand. It does not attempt to apply such an approach to any specific issue. Rather it summarises the core principles behind effective rights regimes (illustrated by the evolution of rights over time), reviews how such regimes have been applied to environmental issues internationally, and describes current natural resource rights regimes in New Zealand. The purpose of applying property rights to the environment can vary widely and reflect quite different perspectives. Regulation by any form, however, whether command-and-control or market-based, creates or modifies property rights. While private property rights will not always be appropriate, the alternatives redefine and reallocate rights rather than eliminating them. A common or public property right remains a right held by someone. The choice is not therefore whether to modify property rights to improve environmental outcomes, but how to do so in a way that optimises national welfare. However, if more use of market-based instruments is appropriate, then the work required to create the legal, institutional and scientific framework to successfully implement them (including trading off social, economic and environmental outcomes) should not be under-estimated. Fishing and water rights demonstrate these difficulties and the payoff (for fisheries at least) that can be achieved.
Keywords: D23; H23; P14; Q15; Q24; 330; Property Rights; Transferability; Market Based Instruments (MBI); Environmental Policy; New Zealand